Biphasic contrast-enhanced [18F]PSMA-1007 PET/CT imaging to improve the detection of local relapse of prostate cancer - Eduards Mamlins; Emil Novruzov; Tadashi Watabe; Yuriko Mori; Mardjan Dabir; Katalin Mattes-György; Christina Antke; Jan Henke; Matthias Boschheidgen; Julian Kirchner; Danny Jazmati; Jan Hausmann; et al. (EJNMMI Research)
Abstract Background The implementation of PSMA imaging in prostate cancer (PC) management has significantly improved the medical care of patients owing to its clinical impact, particularly with respect to biochemical recurrence. However, there is still an unmet clinical need regarding the correct discrimination of equivocal, centrally located, focal [18F]PSMA-1007 uptake without any CT-morphological findings in the postsurgical prostate bed. The aim of this monocentric, retrospective study was to investigate the efficacy of a biphasic, contrast-enhanced [18F]PSMA-1007 acquisition protocol. Results This study investigated a total of 24 biologically male patients with BCR, with a mean PSA level of 0.96 ng/ml at the time of recurrence. The presence of local relapse was regarded as consistent by biphasic, contrast-enhanced [18F]PSMA-1007 PET/CT scans, of which 22 cases were finally validated through the composite reference standard after a 2-years follow-up. The acquisition of whole-body, contrast-enhanced PET/CT imaging data was performed after a mean of 105 (± 19) minutes, whereas late-phase PET/CT imaging of the pelvis with low-dose CT was conducted after 140 min (± 10) on average following the intravenous application of [18F]PSMA-1007 (injected mean activity of 240 MBq (± 29)). The median SUVmax and SUVmean values of local relapse increased by 26% and 5%, respectively, in late-phase images. Moreover, median TBR with respect to the obturator internus muscle seemed to benefit the most from late-phase imaging, with an increase of 185%. The dynamics of the SUV metrics and TBR in lesions were statistically significant (P value < 0.001–0.019). Moreover, the retrospective reading of delayed [18F]PSMA-1007 PET/CT imaging provided an upgrade of the reporting for suspected local PC relapse from a previous PSMA-RADS 3A to a later PSMA-RADS 5 in seven patients (29%), unless the impact of contrast agent in the urethra would also be considered equally important. For the remaining patients, the qualitative evaluation of contrast agent displacement in the urethra was necessary for a final clinical decision that provided the upgrading of the reporting to PSMA RADS 5 for an additional nine patients (38%). Conclusions Given the aforementioned, highly specific unmet clinical need for a relatively small ratio of patients with prostate cancer undergoing PSMA imaging, our proposed acquisition protocol mandates a well-balanced preselection of patients. Under this premise, the study results demonstrated that the optimized acquisition protocol with biphasic contrast-enhanced [18F]PSMA-1007 PET/CT imaging improved the diagnostic performance for the detection of local PC recurrence in 67% of preselected patients.